A comparative study of thermal characteristics of GaN-based VCSELs with three different typical structures. (12th December 2017) - Mei, Yang; Xu, Rong-Bin; Xu, Huan; Ying, Lei-Ying; Zheng, Zhi-Wei; Zhang, Bao-Ping; Li, Mo; Zhang, Jian
Abstract: Thermal characteristics of GaN-based vertical cavity surface emitting lasers (VCSELs) with three typical structures were investigated both theoretically and experimentally. The simulation results based on a steady state quasi three-dimensional cylindrical model show that the thermal resistance ( R th ) is affected by cavity length, mesa size, as well as the bottom distributed Bragg reflector (DBR) size, and the detail further depends on different structures. Among different devices, GaN VCSEL with a hybrid cavity formed by one nitride bottom DBR and another dielectric top DBR is featured with lower R th, which is meanwhile affected strongly by the materials of the epitaxial bottom DBR. The main issues affecting the thermal dissipation in VCSELs with double dielectric DBRs are the bottom dielectric DBR and the dielectric current-confinement layer. To validate the simulation results, GaN-based VCSEL bonded on a copper plate was fabricated. R th of this device was measured and the results agreed well with the simulation. This work provides a better understanding of the thermal characteristics of GaN-based VCSELs and is useful in optimizing the structure design and improving the device performance.